Development of a Scout Guide Based on Local Wisdom and Religious Moderation at MTsN Agam Regency: Realizing Tolerance and Unity in Character Education - Salim, Agus; Iswantir; Januar; Zulfiani, Muh (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aims to develop a Scout activity guide based on local wisdom and religious moderation at MTsN Agam Regency. The main issue faced is the lack of integration of local wisdom values and the principles of religious moderation into Scout activities, which could strengthen students' character, particularly in fostering tolerance and unity. The approach used in this study is Research and Development (R&D) with the Four-D model (Define, Design, Develop, Disseminate). The first stage, Define, was conducted through needs analysis via observations, interviews with Scout leaders and students, and documentation of Scout activities. The analysis results indicated the need for a guide that integrates Minangkabau local wisdom and religious moderation into Scout activities. The second stage, Design, resulted in a guide design that includes activities based on local values such as pasambahan, makan bajamba, and musyawarah nagari. In the Develop stage, the designed guide was trialed at four MTsN in Agam Regency, with an average practicality score of 0.90, indicating that the guide is highly practical and well-received. The final stage, Disseminate, involved socialization and training for Scout leaders, ensuring the broader application of the guide. The expert validation score reached 88.5%, and the trial results showed an improvement in students' understanding, with an average posttest score of 91.08. Based on these findings, the study concludes that the integration of local wisdom and religious moderation in Scout extracurricular activities is effective in developing a more tolerant and responsible student character. This research makes a significant contribution to the development of character education based on local culture, relevant to global challenges, and supports the formation of a more inclusive and harmonious society.